PENERAPAN PEMBELAJARANNUMBERED HEADS TOGETHER(NHT) PADA MATERI IKATAN KIMIA - SITI ZULFIA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
The purpose of this article is to describe the application of Numbered Heads Together (NHT) learning, in order to be able to improve student learning outcomes. The research was conducted by giving pre-tests to students to determine students' initial abilities before learning, then subjected to the treatment of the Numbered Heads Together (NHT) learning model. on the subject of Chemical Bonds for 6 hours of lessons with 2 meetings. After finishing the lesson, a post-test was given to determine the improvement of student learning outcomes. The results of observations showed that the activity of researchers in the first cycle of action reached a score of 90% and the results of observing student activities reached 83.75%. While the final test of the second cycle of action obtained students who did not achieve the minimum completeness criteria (KKM) totaled 3 people (10.72%) while students who achieved the completeness criteria scores were 25 people (89.28%), the results of observations on the activities of researchers at The second cycle of action obtained a score of 94.2% and the results of observing student activities reached 93.75%. Thus, it can be concluded that the Numbered Heads Together (NHT) learning model can improve student learning outcomes in the Chemical Bond material. ABSTRAKTujuan artikel ini adalah untuk mendeskripsikan Penerapan Pembelajaran Numbered Heads Together (NHT),agar mampumeningkatkan hasil belajar siswa.Penelitian dilakukan dengan cara memberikan pre-test pada siswa untuk mengetahui kemampuan awal siswa sebelum pembelajaran, selanjutnya dikenakan perlakuan model pembelajaran Numbered Heads Together (NHT) pada materi Ikatan Kimia selama 6 jam pelajaran dengan 2 kali pertemuan. Setelah selesai pembelajaran, diberikan post-test untuk mengetahui peningkatan hasil belajar siswa. Hasil observasi terdapat aktivitas peneliti pada tindakan siklus I mencapai skor 90% dan hasil observasi aktivitas siswa mencapai 83,75%. Sedangkan tes akhir tindakan siklus II diperoleh siswa yang tidak mencapai nilai kriteria ketuntasan minimal (KKM) berjumlah 3 orang (10,72%) sedangkan siswa yang mencapai nilai kriteria ketuntasan berjumlah 25 orang (89,28%), hasil observasi terhadap aktivitas peneliti pada tindakan siklus II memperoleh skor 94,2% dan hasil observasi aktivitas siswa mencapai 93,75%. Dengan demikian dapat disimpulkan bahwa model pembelajaran Numbered Heads Together (NHT) dapat meningkatkan hasil belajar siswa pada materi Ikatan Kimia.